2016
DOI: 10.1002/mnfr.201500769
|View full text |Cite
|
Sign up to set email alerts
|

AllergenOnline: A peer‐reviewed, curated allergen database to assess novel food proteins for potential cross‐reactivity

Abstract: AllergenOnline provides a useful peer-reviewed tool for identifying the primary potential risks of allergy for GMOs and novel foods based on criteria described by the Codex Alimentarius Commission (2003).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
104
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 165 publications
(106 citation statements)
references
References 82 publications
1
104
0
1
Order By: Relevance
“…The AOL database (http://www.allergenonline.org/) is a peer‐reviewed allergen list and sequence database that is updated each year . We used the AOL as the primary tool in searching for matches to allergenic sequences.…”
Section: Methodsmentioning
confidence: 99%
“…The AOL database (http://www.allergenonline.org/) is a peer‐reviewed allergen list and sequence database that is updated each year . We used the AOL as the primary tool in searching for matches to allergenic sequences.…”
Section: Methodsmentioning
confidence: 99%
“…The allergen database most often used currently in the assessment of novel proteins is the Allergen Online database from the Food Allergy Research and Resource Program (FARRP; www.allergenonline.org). It is updated annually and curated based on predefined criteria (Goodman et al, 2016). On the same concept, a new database called COMPARE is being built by the Health and Environment Science Institute (HESI) and aims to be a publicly accessible and transparent resource of allergens (HESI, 2016).…”
Section: Bioinformatics Approachesmentioning
confidence: 99%
“…The database was developed within the Food Allergy Research and Resource Program (FARRP) at the University of Nebraska [46]. For each allergen, data on source organism, common name, IUIS official nomenclature, protein length, class of allergen like food allergen, contact allergen, etc., and a link to the NCBI protein (GenPept) [32] database are provided.…”
Section: Allergenonline Databasementioning
confidence: 99%
“…Allermatch [66], AllerTool [67], and AllergenPro [53] are some of the prominent web servers which employ these FAO/WHO guidelines for allergen prediction. Additionally, some of the major allergen databases such as SDAP [41] and AllergenOnline [46] also utilize this strategy for allergenicity prediction. A recent study performed by Verma et al [68] has shown that the sequence similarity-based approach gives substantially better results when used in combination with other bioinformatics methods.…”
Section: Sequence Similarity-based Approachesmentioning
confidence: 99%